Pengaruh Keamanan, Fitur Layanan dan Harga terhadap Keputusan Menggunakan Jasa Transportasi Online Grab : (Studi Kasus Pada Masyarakat Desa Bangun Sari Tanjung Morawa Deli Serdang) - Rodiah Marpaung; Mutawaqil Bilah Tumanggor (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this research is to determine the influence of security, service features and price on purchasing decisions among the people of Bangun Sari Village, Tanjung Morawa, Deli Serdang. The sample used in this research was 100 respondents who had made orders on the Grab application. The data used in this research is primary data obtained from questionnaires. This research uses quantitative methods with survey techniques. The sampling technique uses non-probability sampling with purposive sampling which uses several criteria. To determine the influence of security, service features and price on purchasing decisions among the people of Bangun Sari Village, Tanjung Morawa, Deli Serdang. Meanwhile, the data analysis method used in this research is the multiple linear regression analysis method which was carried out with the help of computer software, namely the Statistical Package For Social Science (SPSS 23). The results of this research show that: (1) Security partially and significantly influences purchasing decisions. (2) Service features partially and significantly influence purchasing decisions. (3) Prices partially and significantly influence Village Fund Accountability. (4) Security, Service Features and Prices simultaneously and significantly influence Village Fund Accountability.